Spiral Scan Order based Vector Quantization for Compressing Medical Test Image - Rani, M. Mary Shanthi; Chitra, P (International Journal of Computer Sciences and Engineering, 2025)
The rapid growth of technology needs massive data storage for online transmission. Medical data occupies huge space for storage which has to be reduced for effective transmission, specifically for telemedicine applications. This emphasises the need of image compression which creates extra storage space to store more data. This paper presents a novel implementation of vector quantization using spiral scan order for enhancing the quality and compression as well. The standard metrics like Peak Signal to Noise Ratio (PSNR), Structural Similarity (SSIM), Compression Ratio (CR) and Bit Rate (BR) are used to evaluate the performance of the proposed method. Experimental results demonstrate the merits of the proposed method in terms of compression metrics than other existing methods